Doping of Mn2VAl and Mn2VSi Heusler alloys as a route to half-metallic antiferromagnetism - Galanakis, I.; Ozdogan, K.; Sasioglu, E.; Aktas, B. (Amer Physical Soc, 2007)
Half-metallic antiferromagnets are the ideal materials for spintronic applications since their zero magnetization leads to lower stray fields and thus tiny energy losses. Starting from the Mn2VAl and Mn2VSi alloys we substitute Co and Fe for Mn and we show by means of first-principles electronic structure calculations that the resulting compounds are ferrimagnets. When the total number of valence electrons reaches the magic number of 24 the Fe-doped compounds are semimetals and thus nonmagnetic while the Co-doped ones show the desirable half-metallic antiferromagnetic character. The compounds are very likely to be synthesized experimentally since the parent compounds Mn2VAl and Co2VAl have been already grown in the Heusler L2(1) lattice structure.
Keywords: Electronic-Structure; Magnetic-Properties; Mn(2)Vz Z; Al; Ferrimagnetism; Behavior; Search; Ga; Ge; Si